Некоторые аспекты инвестирования в Севастополь - Мельников, В.И. (Культура народов Причерноморья, 2013)
Инвестирование финансовых средств в экономику городов или регионов всегда сопряжено с целым рядом проблем и трудностей. Севастополь, в этом плане, не является исключением, но по сравнению с другими городами Украины обладает целым рядом несомненных преимуществ. Это, в первую очередь, географическое положение, наличие достаточно большого количества защищенных от ветров незамерзающих бухт, богатое историческое наследие, значительный промышленный потенциал и квалифицированная рабочая сила. Эти условия позволяют городу развивать рыбодобывающие и рыбоперерабатывающие отрасли, строительные и промышленные предприятия, исторический туризм, а природно-климатические условия, являются хорошей базой развития туризма, включающего яхтинг, спелеологию, альпинизм, дайвинг. Інвестування фінансових ресурсів в економіку міст або регіонів завжди пов’язано з цілим рядом проблем і труднощів. Севастополь, у цьому плані, не є виключенням, але в порівнянні з іншими містами України має цілий ряд безсумнівних переваг. Це, у першу чергу, географічне положення, наявність досить великої кількості захищених від вітрів незамерзаючих бухт, багата історична спадщина, значний промисловий потенціал і кваліфікована робоча сила. Ці умови дозволяють місту розвивати рибодобувні й рибопереробні галузі, будівельні й промислові підприємства, історичний туризм, а природно-кліматичні умови є гарною базою розвитку туризму, яка включає яхтінг, спелеологію, альпінізм, дайвінг. Investing financial means into the economy of separate cities or regions is always combined with a series of problems and difficulties. Sevastopol is not an exception, but in comparison with other cities of Ukraine, it possesses a large number of definite advantages. These are, first of all, geographical location; many protected from the winds and ice-free bays, rich historical heritage, significant industrial potential and highly skilled labor force. These conditions allow the city to develop fishing and fish-processing branches, construction and industrial enterprises, as well as the heroic history of the hero-city makes it possible to develop historical tourism, and natural climatic conditions appear to be a perfect basis of developing tourism, including yachting, speleology, mountain climbing, and diving. In this connection, the attempt to examine and analyze priority investment trends in economic development of Sevastopol on the basis of the existing and developing industries is undertaken. The unstable situation in the economy and policy do not attract potential investors, since conditions for safe business are not created. The investors who arrived into the Sevastopol region earlier took the most attractive objects for the investment and today they retain their positions. The appearance of new investors will unavoidably entail the property redistribution and spheres of influence.